The Impact of Endometriosis and Its Treatment on Ovarian Reserve - Seyhan, Ayse; Ata, Baris; Uncu, Gürkan (Seminars in Reproductive Medicine, 2015)
Endometriosis is a chronic disease mostly affecting women at reproductive age. There is a clear association between endometriosis and infertility; however, exact mechanisms are unknown. Some evidence suggests an adverse effect on oocytes. Endometriosis and its surgical treatment can affect quantitative ovarian reserve as well. In the presence of endometriomas, serum level of anti-Müllerian hormone (AMH) seems a more reliable marker of ovarian reserve than antral follicle count. Women with endometrioma have decreased serum AMH levels as compared with healthy controls. This is further declined after surgical excision, and the decline seems permanent. Bipolar cauterization of the ovary seems to be playing a role on ovarian damage. Extraovarian endometriosis and its surgical treatment can also be associated with decreased ovarian reserve, but there is limited information. Patients with endometriosis should be informed about fertility preservation options, especially in the presence of bilateral endometriomas or prior to surgery.
Keywords: endometriosis; endometrioma; surgery; AMH; AFC; ovarian reserve